Effects of co-cultured common carp on nutrients and food web dynamics in rohu aquaculture ponds - Rahman, Mohammad Mustafizur (Inter-Research, 2015)
Using the common carp Cyprinus carpio L. in polyculture ponds to increase both phyto- and zooplankton availability has become a popular practice for the cultivation of planktivorous fish, such as rohu Labeo rohita Hamilton. However, the dynamics of how common carp influences the environment and ecology in polyculture ponds are unclear. In the present study, the effects of various stocking densities (0, 0.5 and 1 m−2) of common carp on the dynamics of nutrients, phytoplankton, zooplankton and benthic macroinvertebrates were investigated every other week over a 137 d period in rohu (density: 1.5 m−2) ponds under fed and unfed conditions. All environmental parameters and all groups of phytoplankton, zooplankton and benthic macroinvertebrates significantly changed over time, although trends in these changes were inconsistent at different common carp densities. The correlation between phosphate-phosphorus (PO4-P) and total phytoplankton biomass indicated that the phytoplankton biomass was limited by low PO4-P concentrations in ponds without common carp. Common carp-driven resuspension increased N and P fluxes from the sediment to the water column and subsequently increased primary and secondary production. A stocking density of 0.5 common carp m−2 had strong effects on nutrients and both phyto- and zooplankton availability, with an increasing trend over time. These effects were partially lost in ponds with 1 common carp m−2, which can be considered as overstocking. This study suggests that an optimal density of common carp can be used as a management tool to manipulate the aquaculture environment for better growth and production of fish.